Study on the Experience of Public Health System Construction in China's COVID-19 Prevention - Zhang, Pengfei (Frontiers in Public Health, 2021)
Background: China's experience in the process of COVID-19 prevention provides a reference for other countries in the world. This article studied the experience of public health system construction in China's COVID-19 prevention. Methods: Based on literature review and theoretical analysis, this paper constructs a theoretical framework of national public health system construction in health crisis. Based on this theoretical framework, combined with the policies and measures formulated by the Chinese government in the process of COVID-19 prevention, this article evaluate the advantages and deficiencies of China's public health system construction in response to COVID-19. Results: The Chinese government ensured the adequate supply of health resources, improved people's ability to pay medical expenses, and adopted advanced public health propaganda methods based on the Internet to help people grasp the basic information and development trend of COVID-19 in the process of COVID-19 prevention. At the same time, the utilization efficiency of health resources was low in China, people's ability to pay for medical expenses was unequal, and the disclosure of virus information in the early stage of the outbreak of COVID-19 is not timely. Conclusions: Other countries can learn from the advantages of China’s public health system construction and avoid China’s deficiencies in the process of public health system construction, which will help them improve the efficiency of COVID-19 prevention.